Progress of ecological tourism trends (Journal of Geography and Environmental Management, 2016)
Basic directions of ecological tourism are presented in this article, especially on development of ecological tourism of Kazakhstan, basic conceptions of ecological tourism, especially guarded natural territories and state national parks, activity of the especially guarded natural territories and progress of ecological tourism trend is considered in Kazakhstan.
Keywords: ecological tourism